2010
DOI: 10.1007/s12033-010-9280-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Promoter Analysis of a Cotton RING-Type Ubiquitin Ligase (E3) Gene

Abstract: A cotton fiber cDNA, GhRING1, and its corresponding gene have been cloned and characterized. The GhRING1 gene encodes a RING-type ubiquitin ligase (E3) containing 338 amino acids (aa). The GhRING1 protein contains a RING finger motif with conserved cysteine and histine residues at the C-terminus, and is classified as a C(3)H(2)C(3)-type RING protein. Blast searches show that GhRING1 has the highest homology to At3g19950, a zinc finger family protein from Arabidopsis. Real time RT-PCR analysis indicates that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The overexpression of rice SUMO E3 ligase gene OsSIZ1 in cotton improved fiber yield (Mishra et al 2017). Similarly, GhRING1 transcript levels were significantly elevated in elongating fibers at 15 DPA (Ho et al 2010). Our findings together with these previous findings, demonstrate the suitability of G. hirsutum RH2FE3 genes for quantitative studies at different cotton fiber developmental stages.…”
Section: Fiber-specific Expression Profiles Of Rh2fe3 Genessupporting
confidence: 76%
See 1 more Smart Citation
“…The overexpression of rice SUMO E3 ligase gene OsSIZ1 in cotton improved fiber yield (Mishra et al 2017). Similarly, GhRING1 transcript levels were significantly elevated in elongating fibers at 15 DPA (Ho et al 2010). Our findings together with these previous findings, demonstrate the suitability of G. hirsutum RH2FE3 genes for quantitative studies at different cotton fiber developmental stages.…”
Section: Fiber-specific Expression Profiles Of Rh2fe3 Genessupporting
confidence: 76%
“…E3 ligases have roles in fiber cell elongation. For example, in Gossypium hirsutum (upland cotton), high transcript level of GhRING1 was observed at 15 days post-anthesis in cotton fiber and GhRING1 encodes an E3 ligase (Ho et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The three genes were all expressed in fiber in a developmentally regulated manner. The E. coli over-expressed GhRING1 was found to have the ubiquitin E3 ligase activity by an in vitro reconstitution assay [21]. These data suggested that cotton fiber growth and development are regulated via protein ubiquitination and protein ubiquitination may play a role in fiber differentiation.…”
Section: Introductionmentioning
confidence: 84%
“…The differential expression of two E2 genes, GhUBC1 and GhUBC2 [20], and the GhRING1 [21] and GhRING2 genes in cotton fiber cells strongly suggests that cotton fiber growth and development may be regulated by protein ubiquitination. Hovav et al [38] and Al-Ghazi et al [39] have shown that several hundred genes involved in the ubiquitin-mediated protein degradation pathway, including genes for the subunits of proteasome, E2, SCF F-box proteins, and RING-type ubiquitin E3 ligases were highly up-regulated in fiber at the elongation and the secondary cell wall synthesis stages.…”
Section: Protein Ubiquitination and Fiber Developmentmentioning
confidence: 99%
See 1 more Smart Citation